Mammographic density and risk of breast cancer in Korean women. Issue 5 (September 2015) - Kim, Bo-Kyoung; Choi, Yoon-Ho; Nguyen, Tuong L.; Nam, Seok Jin; Lee, Jeong Eon; Hopper, John L.; Sung, Joohon; Song, Yun-Mi
<x xml:space="preserve">Abstract</x> We carried out this study to evaluate the association between mammographic density adjusted for age and BMI and early-onset breast cancer in Asian women. We recruited 213 Korean patients with breast cancer (45% diagnosed before the age of 50 years) and 630 controls matched for age, menopausal status, and examination date. The percentage and absolute size of dense areas on digital mammograms were measured using a computer-assisted thresholding technique (Cumulus). We carried out an analysis using the conditional logistic regression model with adjustment for covariates. An increase by 1 SD in age and BMI-adjusted absolute dense area and percentage dense area was associated with a 1.15-fold (95% confidence interval: 1.03, 1.29) and 1.20-fold (95% confidence interval: 1.06, 1.37) increased risk of breast cancer, respectively. These associations were stronger for premenopausal disease (P=0.07 and 0.01, respectively) and for disease diagnosed before age 50 (P=0.07 and 0.02, respectively) than for postmenopausal disease (P=0.16 and 0.23, respectively) or later onset disease (P=0.10 and 0.10, respectively). There was no difference in the associations with premenopausal versus postmenopausal and early-onset versus late-onset disease. After adjusting for age and BMI, both a greater absolute dense area and a greater percentage dense area were associated with an increased risk of breast cancer, particularly at a young age.